RANCANG BANGUN DAN PEMANFAATAN MIKROTIK DALAM JARINGAN RT RW NET - Rahayu Nugraheni Rachmawati; Titi Christiana (Pusat Riset dan Inovasi Nasional, 2022)
Jl. Medokan Sawah RT 02 / RW 01 Kota Jakarta is a densely populated environment, the people are very hungry for fast and accurate information. This internet is available which is relatively expensive as the main choice in finding the information needed. However, the cost is very expensive for a connection that must be paid every month. Although there are currently many available CDMA and GSM modems circulating in the market, it is not enough to meet the need for the speed of an internet connection. Even though there are internet cafes that have been established, it is still not efficient for the cost and time of internet users in the area. The purpose of this study is to save bandwidth rental costs per month for unlimited connections, provide stable internet connections that can be used for 24 hours, provide data transfer with bandwidth management, thus guaranteeing the quality of internet connections. The system development method used is Prototyping whose stages include identifying user needs, making a prototype, user approval, and using a prototype. As a server, using Mikrotik Os where in Mikrotik Os there are several important and interesting features provided by Mikrotik itself, among these features are bandwidth management, firewall, DNS client caching, and many other features provided by Mikrotik. With this Mikrotik provides stable internet data transfer in accordance with the management of Mikrotik Os as a server. The client uses a windows-based operating system, this is because the tool drivers used are more compatible with the windows operating system compared to using a linux-based operating system, because they have to compile drivers.